Q. 5 C4.0( 18 Votes )

<span lang="EN-US

Answer :

Let g(x) = 3

And p(x) = 3x + 3


Then, dividing p(x) by g(x) gives


q(x) = x + 1


and,


r(x) = 0


Deg(r(x)) = 0


Hence,


g(x) = 3


p(x) = 3x + 3


q(x) = x + 1


r(x) = 0


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

Divide the AP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics